1999
DOI: 10.1074/jbc.274.26.18387
|View full text |Cite
|
Sign up to set email alerts
|

Sigma Receptor Photolabeling and Sigma Receptor-mediated Modulation of Potassium Channels in Tumor Cells

Abstract: Recent work has indicated that sigma receptor ligands can modulate potassium channels. However, the only sigma receptor characterized at the molecular level has a novel structure unlike any other receptor known to modulate ion channels. This 26-kDa protein has a hydropathy profile suggestive of a single membranespanning domain, with no apparent regions capable of G-protein activation or protein phosphorylation. In the present study patch clamp techniques and photoaffinity labeling were used in DMS-114 cells (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 28 publications
6
52
0
Order By: Relevance
“…Modulation of K ϩ channels by pentazocine or SKF10047 persisted although nerve terminals were internally perfused with GTPfree solutions, the G-protein inhibitor GDP␤S, or the G-protein activator GTP␥S. In DMS-114 cells (a tumor cell line isolated from a small-cell lung carcinoma), perfusion with GDP␤S also failed to alter the response to SKF10047 (65). Similar negative results were obtained in tests for protein kinase involvement.…”
Section: Physiology and Pathophysiology Of Receptorssupporting
confidence: 60%
See 2 more Smart Citations
“…Modulation of K ϩ channels by pentazocine or SKF10047 persisted although nerve terminals were internally perfused with GTPfree solutions, the G-protein inhibitor GDP␤S, or the G-protein activator GTP␥S. In DMS-114 cells (a tumor cell line isolated from a small-cell lung carcinoma), perfusion with GDP␤S also failed to alter the response to SKF10047 (65). Similar negative results were obtained in tests for protein kinase involvement.…”
Section: Physiology and Pathophysiology Of Receptorssupporting
confidence: 60%
“…Internal perfusion of nerve terminals with the non-hydrolysable ATP analog AMPPcP had no effect on K ϩ current inhibition by 1 receptor drugs. Of particular significance was the observation that K ϩ channels present in excised outside-out patches were modulated by SKF10047 (64,65). This effect excluded a role for any soluble cytoplasmic factor.…”
Section: Physiology and Pathophysiology Of Receptorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, from rat cortical synaptosomes, C6 glioma cells (74) or NCB-20 cells (127), DTG, (+)3-PPP, and haloperidol have been shown to facilitate hyperpolarization with a reversal potential corresponding to that of K + or to block tonic outward K + currents. In rat neurohypophysis, Wilke et al (128) have confirmed this notion by providing evidence that (+)pentazocine and (+)SKF-10,047 as well as DTG and haloperidol, but not DHEAS or progesterone, elicited a marked inhibition of K + currents. This latter study then suggested that σ drugs and steroids may act distinctly at the molecular level.…”
Section: 2supporting
confidence: 56%
“…+ currents An interaction between sigma receptors and K + channels was suggested by the observation that the sigma ligands DTG and (+)-pentazocine inhibited K + currents (50,53,54). Further investigations of this modulation suggested that a protein-protein interaction is the likely mechanism of signal transduction by sigma receptors as sigma ligands did not interact directly with K + channels (43,54).…”
Section: Modulation Of Kmentioning
confidence: 99%